The Effect of Vermicompost Fertilizer and EM4 (Effective Microorganism) On The Growth and Production of tomato (Lycopersicon esculentum). - M Abror; Widyastuti (Nabatia, 2019)
The study aimed to determine the effect of vermicompost fertilizer and EM4 on the growth and production of tomato (Lycopersicon esculentum). This research was conducted in the village of Penatarsewu Tanggulangin District Sidoarjo Regency, start from October 2018 until January 2019. Experiments are arranged factorially by using a Randomized Environmental Plan (RAK) which was repeated three times. The first factor is the dose vermicompost fertilizer 100 gr/plant (D1), t 200 gr/plant (D2), 300 gr/plant (D3) and 400 gr/plant (D4). The second factor with EM4 that is without EM4 (E0) and with EM4 (E1). The variables observed are plant high, stem diameter, number of leaves, leaf area, number of fruits, fruit weight, and plant weight. The results show that interaction the observation of plant high, the dose vermicompost fertilizer significant effect of observation number of leaves, leaf area, number of fruits, fruit weight, and plant weight. The gift EM4 signifi- cant effect of observation plant high and number of leaves. The results of the study say that treatment dose vermicompost fertilizer 400 gr/plant (D4) and giving EM4 (E1) on the growth and production of tomato is better.